(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The buffer zone is an active component of the riverbank. It is the boundary between the bank and the river. Any damage that occurs in the buffer zone causes a number of problems in its natural and ecological structure. Most of these problems are diagnosable and observed in the outer space of the buffer zone. The appearance of these problems is in varying proportions depending on the type of human intervention in them. This intervention can have a negative effect on the riverbank on the one hand and on the river on the other. In light of this, studies have been directed towards examining various ecological mechanisms that ensure the safety of dealing with outer spaces in river buffer areas. The main research problem is represented in the lack of ecological value of the buffer zone in Abu Nuwas area in Baghdad City, as well as the lack of urban and design treatments causing a huge challenge of integration between the river and the city. In addition, the lack of connectivity with the buffer zone, which is a basic component connecting the water to the land. Moreover, few studies have dealt with this topic in studying the strategies of the landscape ecology of in the river buffer zone of Baghdad City. Thus, the research objective is to determine the mechanisms and indicators of the ecology of outer space, and apply them at the edge of the Tigris River (as a case study). Represented by Abu Nuwas area and park in Baghdad City, with the aim of further diagnosis of the situation of the buffer zone and the extent to which ecological values are applied. The results of the research in both its theoretical and practical aspects have produced a clear approach to ecological strategies that achieve buffer zone ecology and the development of specific mechanisms to provide a safe and effective river environment that accommodates various events and uses in the buffer zone, and enhance public awareness of its importance. The buffer zone is an active component of the riverbank. It is the boundary between the bank and the river. Any damage that occurs in the buffer zone causes a number of problems in its natural and ecological structure. Most of these problems are diagnosable and observed in the outer space of the buffer zone. The appearance of these problems is in varying proportions depending on the type of human intervention in them. This intervention can have a negative effect on the riverbank on the one hand and on the river on the other. In light of this, studies have been directed towards examining various ecological mechanisms that ensure the safety of dealing with outer spaces in river buffer areas. The main research problem is represented in the lack of ecological value of the buffer zone in Abu Nuwas area in Baghdad City, as well as the lack of urban and design treatments causing a huge challenge of integration between the river and the city. In addition, the lack of connectivity with the buffer zone, which is a basic component connecting the water to the land. Moreover, few studies have dealt with this topic in studying the strategies of the landscape ecology of in the river buffer zone of Baghdad City. Thus, the research objective is to determine the mechanisms and indicators of the ecology of outer space, and apply them at the edge of the Tigris River (as a case study). Represented by Abu Nuwas area and park in Baghdad City, with the aim of further diagnosis of the situation of the buffer zone and the extent to which ecological values are applied. The results of the research in both its theoretical and practical aspects have produced a clear approach to ecological strategies that achieve buffer zone ecology and the development of specific mechanisms to provide a safe and effective river environment that accommodates various events and uses in the buffer zone, and enhance public awareness of its importance.